Performance and biological response of middle-power under hyperbaric hyperoxic conditions in judo athletes - pilot studies - Takezawa, T. (Archives of Budo, 2021)
Background and Study Aim: Judo athletes are required to compete at maximum performance for 4-5 min in most competitions. In addition, various energy supply mechanisms are used in judo because it requires a proper combination of complex and competition-specific muscle strength due to its competitive characteristic. However, considering the competition-time glycolysis, middle-power is thought to be the main mechanism that is utilized. In recent years, hyperbaric oxygen therapy (HBO), which is useful for recovering physical function, has been reported as a training device. Although no effect has been observed in high-power training, performance is shown to be significantly improved in 30-s middle-power training. Therefore, we set up 60-s middle-power training, similar to a judo match, under normobaric normoxia (NN) and hyperbaric hyperoxia (HH) environments. The purpose of this study is knowledge about the performance of judo athletes and them biological response of a normal pressure, normal oxygen environment (normobaric normoxia, NN) and hyperbaric high oxygen environment (hyperbaric hyperoxia, HH) while exerting middle-power for 60 seconds.